(untitled) (Journal of Oriental Studies, 2018)
Legal language is the most complicated and hard to understand version of the standard language due to its lexicon, terminology as well as syntactical features. Therefore, the use, comprehension and interpretation of this language by non-specialists is very difficult. Turkish, as a language of science, has reached today the competence to express the most complicated legal relations because of its vocabulary and terminological basis. This article primarily deals with the terminological basis and vocabulary of the modern Turkish legal language also taking into consideration their historical formation.